Isolation and characterization of protease from Bacillus subtilis 1012M15 - ELFI SUSANTI VH (Biodiversitas Journal of Biological Diversity, 2003)
A local strain of Bacillus sp. BAC4, is known to produce penicillin G acylase (PGA) enzyme with relatively high activity. This strain secretes the PGA into the culture medium. However, it has been reported that PGA activity fall and rise during culture, and the activity plummets during storege at â€“200C, which probably due to usage protease activity of Bacillus sp. BAC4. To study the possible use of Bacillus subtilis 1012M15 as a host cell for cloning the pga gene from Bacillus sp. BAC4, the protease activity of Bacillus subtilis 1012M15 were studied. Protease activity was determined by Horikoshi method. In this experiment, maximum protease activity in Bacillus subtilis 1012M15 culture was obsereved after 8 hours. At this optimum condition, protease activity of Bacillus sp. BAC4 is five time higher than that of Bacillus subtilis 1012M15. This situation promised the possible usage of Bacillus subtilis 1012M15 as a host cell for pga expression. For protease characterization, the bacterial culture had been separated from the cell debris by centrifugation. The filtrate was concentrated by freeze drying, fractionated by ammonium sulphate, dialyzed in selovan tube, and then fractionated by ion exchance chromatography employing DEAE-cellulose. The five peaks resulted indicated the presence of five protease. Based on inhibitor and activator influence analysis, it could be concluded that proteases from Bacillus subtilis 1012M15 contained of serin protease as well as metalloprotease and serin protease mixture.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: protease, penicillin G acylase, cloning, host cell.